Inequality, green spaces, and pregnant women: Roles of ethnicity and individual and neighbourhood socioeconomic status - Dadvand, Payam; Wright, John; Martinez, David; Basagaña, Xavier; McEachan, Rosemary R.C.; Cirach, Marta; Gidlow, Christopher J.; de Hoogh, Kees; Gražulevičienė, Regina; Nieuwenhuijsen, Mark J. (Environment international, 2014)
Evidence of the impact of green spaces on pregnancy outcomes is limited with no report on how this impact might vary by ethnicity. We investigated the association between residential surrounding greenness and proximity to green spaces and birth weight and explored the modification of this association by ethnicity and indicators of individual (maternal education) and neighbourhood (Index of Multiple Deprivation) socioeconomic status. Our study was based on 10,780 singleton live-births from the Born in Bradford cohort, UK (2007–2010). We defined residential surrounding greenness as average of satellite-based Normalized Difference Vegetation Index (NDVI) in buffers of 50m, 100m, 250m, 500m and 1000m around each maternal home address. Residential proximity to green spaces was defined as living within 300m of a green space with an area of ≥5000m2. We utilized mixed effects models to estimate adjusted change in birth weight associated with residential surrounding greenness as well as proximity to green spaces. We found a positive association between birth weight and residential surrounding greenness. Furthermore, we observed an interaction between ethnicity and residential surrounding greenness in that for White British participants there was a positive association between birth weight and residential surrounding greenness whereas for participants of Pakistani origin there was no such an association. For surrounding greenness in larger buffers (500m and 1000m) there were some indications of stronger associations for participants with lower education and those living in more deprived neighbourhoods which were not replicated for surrounding greenness in smaller buffer sizes (i.e. 50m, 100m, and 250m). The findings for residential proximity to a green space were not conclusive. Our study showed that residential surrounding greenness is associated with better foetal growth and this association could vary between different ethnic and socioeconomic groups. •Limited evidence on impacts of green spaces on foetal growth•Higher residential surrounding greenness was associated with higher birth weight.•Such benefit was observed only for White British, but not those of Pakistani origin.•Subjects with lower individual and neighbourhood socioeconomic status benefited more.